Educação inclusiva: desafios e possibilidades para a inclusão de alunos com deficiências múltiplas - SANTOS, Alveni Queiroz (2019)
The present research intends to understand the challenges and possibilities of the inclusive education of students with multiple deficiencies in the regular school. For a long time people with multiple disabilities were labeled as demon-possessed individuals being excluded from social living. At present, actions have been directed towards an inclusive education model, where everyone can be included in the regular school without discrimination and without prejudice. The study seeks to bring a discussion of how the process of inclusion of these students in the regular class has been made considering the challenges presented to both the school and the educators regarding the promotion of inclusion. The study aims to show that these students, when adequately cared for by the use of play materials, have the possibility of impotence of the Specialized Educational Assistance and the use of Assistive Technology as a means that favors learning and enables the student to have more autonomy and social inclusion. To analyze the results, a bibliographic research was used, through the reading of several authors that approach the question. The results show that students are enrolled in regular education, but there is still a need for renewal and expansion of pedagogical actions aimed at this public, as well as adaptations in the physical structures of schools. We also believe that educators should take a more inclusive approach to welcoming all students regardless of their motor, intellectual or physical, psychic, cultural and other characteristic.